PRODUK OLAHAN TURUNAN BUDIDAYA CACING MERAH DENGAN TEKNIK VERTIKULTUR PADA AGROWISATA TERPADU DI KECAMATAN UKUI, PELALAWAN - Safitri, Syofiatul; Karneli, Okta; Mandataris, Mandataris; Hapsoh, Hapsoh; Sutikno, Sigit; Andri, Seno; Sulistyani, Andri (Universitas Mataram, 2024)
Red worm farming in the Berkat Usaha Farmer Group has been in existence since 2018. Initially, red worm cultivation was carried out in a simple way, namely with shelves arranged for worm breeding. In 2019, red worm cultivation was developed using verticulture techniques in the form of worm reactors. The abundance of worms produced in this worm farming has not been optimally utilised by the Berkat Usaha Farmer Group. The purpose of this service activity is to provide training and knowledge for the Berkat Usaha Farmer Group in making processed worm derivatives cultivated with the verticulture technique in the form of a worm reactor. The method used in this service is PRA (Participatory Rural Appraisal) which involves community groups in training the processing of worm derivatives produced from the cultivation of the Farmer Group. The Riau University Matching Fund Team and partners provide training as well as assistance for Farmers Groups to be able to develop processed red worm derivative products into products that have high selling value. The processed worm-derived products that have been produced are worm pellets, worm flour and dried worms. All of these worm-derived processed products can be marketed, especially in the fisheries sector, because these products are needed for fish feed. The results of this service are in the form of worm derivative processing knowledge obtained by the Farmer group and processed worm derivative products that are ready to pack, ready to sell.